Fundamentación jurídica para la protección y asistencia de víctimas y testigos en el proceso penal.Quevedo - Mena Espinales, Vanessa Janeth (2015)
The present work of legal research, it takes in order to increase a literal to the National System for Protection and Assistance to Victims and Witnesses concerning the extension of protection time after completion of the process in order to fully protect people which are the subject of a crime and so protectively integrity. This Legal research is divided into six chapters In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the hypothesis in research. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research described in point; the methods used, the types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through research results obtained through interviews with relevant authorities based in Quevedo, in addition to surveys of lawyers in free practice, they know how they are violated by the lack of security without any consideration of the rights of those involved in the National System for Protection and Assistance to Victims and Witnesses The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter speaks of the Proposal, objectives, description of the proposal, beneficiaries and social impact.